Library Promotion and User Engagement in Pandemic Times: The Case of Kazakhstan - Yap, Joseph M. (Scientific and Technical Library of Dnipro National University of Railway Transport named after Academician V. Lazaryan, 2020)
Objectives In these trying times due to the global effect of pandemic, what social media accounts do academic libraries in Kazakhstan maintain and how can they improve their social media engagement to continuously connect with their stakeholders? This report provides an overview of the current status of social media engagement of select academic libraries in Kazakhstan during the COVID-19 crises. This paper will give us a picture about the kinds of online postings shared by these libraries particularly with the use of Facebook. Methods The top two universities ranked by Independent Quality Assurance Agency (IQAA) were considered in this report to compare with the only autonomous organization of education in Kazakhstan. The library social media accounts of these three organizations were investigated to review the number of followers, frequency of posting, and its overall social media engagement. Data collected is publicly available to all potential users, followers, or subscribers. Using the post engagement rate (PER) formula introduced by Socialbakers (2013) and adapted by Peñaflor (2018) & Magno (2016), this report identifies and analyzes the average PER Facebook pages maintained by academic libraries. The engagement metrics looked into the number of interactions and the widest reach possible in every post. All three academic libraries investigated maintain a Facebook page. The other account was just created last February 2020. To compare Facebook data during the pandemic times, public information available from June – August 2020 were measured. Results The social media platforms operated by the academic libraries in Kazakhstan are Facebook, Twitter, Instagram, VK, and YouTube. One of the earliest academic library Facebook accounts established in Kazakhstan started in 2010 with less than 3,000 accumulated followers after ten years. This shows a very slow rise in the number of followers considering an academic population of more than 5, 000 people in 2020. Data revealed that Eurasian National University Library’s Facebook account had a higher PER of 0.83 even if it only debut in 2020 compared to the Facebook page of Nazarbayev University which garnered 0.22 PER. KAZNU Library’s Facebook page had the highest PER of 1.02. Conclusions Facebook is the most popular social media platform across the globe but it is not the case in Kazakhstan. Library marketing and promotion in Kazakhstan needs to be addressed as public relations is not the primary focus. The utilization of social media as a tool for user engagement is not fully developed. One way to look at it is to consider library staffing and identify their marketing background. The pandemic situation must be the turning point of academic libraries to enhance their reach with their stakeholders. It was a test to know the readiness of the library in terms of online communication and interaction.
Keywords: social media; user engagement; academic libraries; pandemic; COVID-19; Kazakhstan